2014
DOI: 10.1186/2193-1801-3-457
|View full text |Cite
|
Sign up to set email alerts
|

Efficient genomic DNA extraction protocol from medicinal rich Passiflora foetida containing high level of polysaccharide and polyphenol

Abstract: In Present work, the main objective is to develop less time consuming protocol for genomic DNA isolation from leaves of Passiflora foetida. Optimized protocol is cost effective, as it avoided use of expensive liquid nitrogen. The important parameters of CTAB buffer composition such as Polyvinylpyrrolidone PVP40000 (without PVP, 1%, 2%, 3.5%, 4.0%, 4.5%, 5.0%), CTAB (w, 1%, 2%, 3%, 4%, 5%), water bath temperature (30°C to 70°C) and duration on water bath for half hr and one and half hr has been optimized. CTAB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Plants also contain substances that have inhibitory effect in PCR, mainly, polysacharides and polyphenolic compounds. Polysacharides are difficult to separate from DNA during the extraction (Porebski et al, 1997;Lade et al, 2014) and in the subsequent PCR they interfere with polymerases. Moreover, phenol, alkaloids, polyphenols Rogers and Bendich (1994) and polysacharides were identified to inhibit enzymes in the PCR or restriction reactions (Barra et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Plants also contain substances that have inhibitory effect in PCR, mainly, polysacharides and polyphenolic compounds. Polysacharides are difficult to separate from DNA during the extraction (Porebski et al, 1997;Lade et al, 2014) and in the subsequent PCR they interfere with polymerases. Moreover, phenol, alkaloids, polyphenols Rogers and Bendich (1994) and polysacharides were identified to inhibit enzymes in the PCR or restriction reactions (Barra et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The longer polymethylene tetramines (Met 6-5-6, Met 6-10-6 and Met 5-10-5) characterized by two 2-methoxybenzyl groups were also effective, but they did not cause a swollen tube tip, pointing out a different mechanism in the inhibition of pollen tube elongation. In a previous study it was found that these polymethylene tetramines act at different cellular levels, as they bind to DNA with a higher affinity than Spm and lead to oxidative stress [40].…”
Section: Exogenous Application Of Natural and Synthetic Pas To The Gementioning
confidence: 99%
“…100 mg of germinated pollen was pulverized with liquid nitrogen to a fine powder and DNA was extracted following CTAB-based protocol as described by [40] …”
Section: 9-preparation Of Pollen Dna and 4'6-diamidino-2-phenylindmentioning
confidence: 99%
“…This result indicates, mainly for Mangabeira, the necessity of using DNA extraction protocols with optimized anti-oxidant concentrations, to decrease its degradation (Silva, 2010). In this context, it is necessary to test several experimental scenarios considering variations in the composition of the extraction buffer as in the process (Lade et al, 2014). Different from the other conditioning, the product of the extractions resulting from foliar tissues was maintained at -20°C.…”
Section: Characteristics Observed During the Dna Extraction Proceduresmentioning
confidence: 99%
“…The adequacy of extraction techniques is often carried out for several species of plants (Edge-Garza et al, 2014;Lade et al, 2014;Mogni et al, 2016), but few or no reference has been made to the proper way of conditioning the foliar tissues, obtained in collection expeditions. The way to preserve the tissue for DNA micro extraction is as important as the choice of the DNA extraction protocol so that, optimizations are necessary to facilitate the operation and ensure a better quality of extracted DNA (Tamari and Hinkley, 2016).…”
mentioning
confidence: 99%